New Mediterranean Biodiversity Records (November, 2016) - CH. MYTILINEOU; E.H.Kh. AKEL; N. BABALI; P. BALISTRERI; M. BARICHE; Y.Ö. BOYACI; L. CILENTI; C. CONSTANTINOU; F. CROCETTA; M. ÇELİK; H. DERELI; C. DOUNAS; et al. (Mediterranean Marine Science, 2016)
In the present Collective Article information on 26 taxa belonging to 8 Phyla and extended from the western Mediterranean to the Levantine Sea are presented. The new records were found in 9 countries as follows: Spain: first record for the Mediterranean of the crab Cancer bellianus; Algeria: further records of the alien fish Lagocephalus sceleratus to the west Algerian waters; Italy: first report on the presence and establishment of the ctenophore Mnemiopsis leidyi in Lessina and Varano Lagoons (W. Adriatic) and of Penaeus aztecus in Corigliano Gulf (Italian Ionian). Moreover, the extension of the distribution range of the polychaete Branchiomma bairdi to W. Sicily as well as that of the crab Ocypode cursor and the bryozoan Catenicella paradoxa to E. Sicily are cited. Slovenia: the record of the rare saccoglossan gastropod Placida cremoniana from Piran (Gulf of Trieste) is the first for the Adriatic; Greece: the native sea slug Eubranchus farrani is the first from the Eastern Mediterranean; many sightings of the bamboo corals Isididae distributed along all the E. Ionian Sea and the establishment of P. aztecus in all Greek waters are also reported for first time; the westernmost extension of the alien urchin Diadema setosum in Cretan waters is cited and new sights of the alien species Goniobranchus annulatus and Pterois miles are shown. Turkey: the alien fish Champsodon capensis is reported for first time from the Aegean Sea and the native acari Agauopsis microrhyncha from the Levantine Sea; a new observation of the alien crab Atergatis roseus in Güllük Bay-Aegean is also mentioned; Cyprus: first records of the alien urchin D. setosum and Lobotes surinamensis in Cypriot waters; Lebanon: several sightings of Monachus monachus from the Lebanese waters indicate a potential better status of the species in the area, Egypt: first records of the alien crab Dorippe quadridens and the alien gastropods Nerita sanguinolenta and Conomurex persicus from the Mediterranean Egyptian waters; extension of the distribution range of Diodora funiculata and Diodora rueppellii and a second record of the alien Nerita sanguinolenta in the same area.